A Comment on the General Theorem of the Second Best - Santoni, G.; Church, A. (Review of Economic Studies, 1972)
G. Santoni, A. Church; A Comment on the General Theorem of the Second Best1, The Review of Economic Studies, Volume 39, Issue 4, 1 September 1972, Pages 527–530